Teachers’ conceptions and beliefs about democracy in schools (Revista Peruana de Investigación Educativa, 2015)
Building democracy in schools is a process in which teachers are fundamental actors. This is because their conceptions and beliefs significantly influence their pedagogical practice. Thus, this study intends to explore teachers’ beliefs about democracy and its role within the educational system. Eight public secondary school teachers where intereviewed for the study. Results show that teachers do not recognize building a democratic society as one of the aims of education. Instead, they perceive entrepreneurship and developing working skills as its principal aims. Most teachers understand democracy only as a government system and not as a way of living. Democracy in the school is understood mainly as involvement in school programs or teacher centered actions. Moreover, teachers consider families cannot contribute to students’ education and believe that school cannot do anything to help students with dysfunctional families. Additionally, they hold beliefs about their role as teachers that distance them from democratic stances and from democratic discipline. Results are discussed focusing on the school role for democratic education.
Keywords: teachers’ beliefs; democracy; democratic school; citizenship education; secondary education